International marketing : an Asia-Pacific perspective - Fletcher, Richard. (Prentice Hall, 1999)
The international marketing environment: the rationale for international marketing; the international economic and financial environment; the cultural environment of international business... The international marketing mix: rresearching international markets, international market selection and entry... International marketing strategy: Gaining competitive advantage overseas; international competitive marketing strategies... Contemporary challenges in international marketing...